Preliminary Power Budget Analysis for Equatorial Low Earth Orbit (LEO) Communication Satellite - Suryanti, Desti Ika; Ramayanti, Sri; Mukhayadi, Mohammad (BRIN Publishing, 2021)
Satellite Technology Center – LAPAN would develop a constellation of 9 communication satellites in a low equatorial orbit. These satellites would perform as data collection platforms for many sensors that spread across the Indonesian territory. The data from the sensors will be downlink to Indonesia’s ground stations in real-time. This research aims to analyze the power budget of those satellites to decide how many solar panels and batteries are required to perform their mission. The method in this research began by calculating the power requirements of each mission per orbit period to estimate power consumption and calculate the power generated by the solar panels. The results of these calculations will be implemented to the power system design to find the satellite solar cells/ panels arrangement and battery capacity allocation. To minimize the development time and cost, the solar array design in this study considers the utilization of previous solar panel design of LAPAN-A series satellites as a design constraint. This study shows the configuration of 3 body-mounted solar panels and 2 deployable solar panels could support the mission operation of communication satellite in the low equatorial orbit. For energy storage, these satellites should be equipped with 28 V Li-ion in the 8Sx3P configuration.